Polydatin inhibits ZEB1‐invoked epithelial‐mesenchymal transition in fructose‐induced liver fibrosis. Issue 22 (15th October 2020) - Zhao, Xiaojuan; Yang, Yanzi; Yu, Hanwen; Wu, Wenyuan; Sun, Yang; Pan, Ying; Kong, Lingdong
Abstract: High fructose intake is a risk factor for liver fibrosis. Polydatin is a main constituent of the rhizome of Polygonum cuspidatum, which has been used in traditional Chinese medicine to treat liver fibrosis. However, the underlying mechanisms of fructose‐driven liver fibrosis as well as the actions of polydatin are not fully understood. In this study, fructose was found to promote zinc finger E‐box binding homeobox 1 (ZEB1) nuclear translocation, decrease microRNA‐203 (miR‐203) expression, increase survivin, activate transforming growth factor β1 (TGF‐β1)/Smad signalling, down‐regulate E‐cadherin, and up‐regulate fibroblast specific protein 1 (FSP1), vimentin, N‐cadherin and collagen I (COL1A1) in rat livers and BRL‐3A cells, in parallel with fructose‐induced liver fibrosis. Furthermore, ZEB1 nuclear translocation‐mediated miR‐203 low‐expression was found to target survivin to activate TGF‐β1/Smad signalling, causing the EMT in fructose‐exposed BRL‐3A cells. Polydatin antagonized ZEB1 nuclear translocation to up‐regulate miR‐203, subsequently blocked survivin‐activated TGF‐β1/Smad signalling, which were consistent with its protection against fructose‐induced EMT and liver fibrosis. These results suggest that ZEB1 nuclear translocation may play an essential role in fructose‐induced EMT in liver fibrosis by targeting survivin to activate TGF‐β1/Smad signalling. The suppression of ZEB1 nuclear translocation by polydatin may be a novel strategy for attenuating the EMT in liver fibrosis associated with high fructose diet.